2018
DOI: 10.3390/lubricants6010008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Slip and Lubrication Regime on the Formation of White Etching Cracks on a Two-Disc Test Rig

Abstract: A common cause for maintenance and downtime in multiple fields of the mechanical transmission industries are premature rolling bearing failures due to white etching cracks (WEC). Within this work, WEC have been successfully recreated on a two-disc test rig under rolling contact loading without additional loading such as hydrogen pre-charging. This paper summarizes the state of the investigations regarding the influence of the slip type and the lubrication regime on the WEC formation on the two-disc test rig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…A short explanation of these failure modes can be found in previous work (Cornel et al, 2018). In addition, the following literature is recommended for a more detailed insight (Bongardt, 2015;van Lier, 2015;Gutiérrez Guzmán et al, 2018;Gutiérrez Guzmán et al, 2020).…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…A short explanation of these failure modes can be found in previous work (Cornel et al, 2018). In addition, the following literature is recommended for a more detailed insight (Bongardt, 2015;van Lier, 2015;Gutiérrez Guzmán et al, 2018;Gutiérrez Guzmán et al, 2020).…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
“…3 In addition to that, it is reported that more WECs formation is observed in severe boundary lubrication regimes. 20,21 Therefore, all the tests in this work were performed in the dynamic PoD tribometer with severe boundary lubrication conditions at a temperature range of 30 −35°C. This study chooses oils by their base stock without any additives and has similar kinematic viscosity.…”
Section: Experimental Methodologymentioning
confidence: 99%
“…However, during actual operating conditions of the WTG bearings, SRR would reach up to ±110%, which creates extreme frictional energy accumulation under severe loading conditions. The contact body, which is sliding with lesser surface velocity and traction force acting in the direction of the motion vector, experiences a negative slip [19]. Pure sliding, along with high shear stress, accelerates the formation of WEAs in the bearing subsurface.…”
Section: Samples and Experimental Parametersmentioning
confidence: 99%